2016
DOI: 10.1007/s11082-016-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

A long-period fibre grating monitor of respiratory volumes for the use in non-invasive mechanical ventilation

Abstract: The ventilators involved in mechanical ventilation are usually equipped with pneumatic sensor detecting patient's own respiratory effort in order to assist spontaneous breathing. However, the interface of the mask with the patient promotes air leaks that affect the measurement of pneumatic variables and hence induces patient-ventilator asynchrony. In this paper we describe a new method and apparatus for continuous monitoring of the respiration based on the measurement of chest wall movements. The proposed solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nine of the retained studies tested the feasibility and accuracy of using an optical sensor-based approach to assess the tidal volume ( Table 2 ) [ 12 , 34 , 50 , 52 , 54 , 55 , 56 , 58 , 60 ]. Noticeably, these studies have been carried out by five independent research groups; thus, some of the reported results appeared redundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the retained studies tested the feasibility and accuracy of using an optical sensor-based approach to assess the tidal volume ( Table 2 ) [ 12 , 34 , 50 , 52 , 54 , 55 , 56 , 58 , 60 ]. Noticeably, these studies have been carried out by five independent research groups; thus, some of the reported results appeared redundant.…”
Section: Discussionmentioning
confidence: 99%
“…Two main sensing principles have been proposed among the studies. The first consists of an optical structure inducing a change in the spectral profile of the light traveling along the sensor due to bending (long-period grating sensors [ 34 , 50 , 58 , 60 ]; few-mode fiber Mach–Zehnder interferometer [ 12 ]) or strain (fiber Bragg grating sensors [ 54 , 55 , 56 ]). These sensors are usually embedded (glued or stitched) in fitting garments or suitable elastic bands, and they are designed to monitor changes in the chest and abdomen curvature/circumference while breathing.…”
Section: Discussionmentioning
confidence: 99%
“…The signal generated by heart activity superposes on the chest-wall-motion signal and in our measurements it is an unwanted part of the signal (Ivanovic and Petrovic 2016). The wavelet filtering method was applied on the drift-less LPG signals to eliminate the heart signal from the respiratory activity, figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to investigate the time relationship between these two signals, and hence test the possibility of using chest-wall motion as a confident triggering mechanism. We paid particular attention to elimination of the heartbeat signal shown to be detrimental for accurate detection of the inhalation and exhalation onsets (Ivanovic and Petrovic 2016).…”
Section: Introductionmentioning
confidence: 99%